DAMPAK LIKUIDITAS DAN PROFITABILITAS HARGA SAHAM PERUSAHAAN MANUFAKTUR PADA LQ-45 - Bongsu Saragih (Program Studi Magister Manajemen Fakultas Ekonomi Universitas Krisnadwipayana, 2019)
Stock price is the value of a stock that reflects the wealth of the company that issued the stock, where changes or fluctuations are largely determined by the strength of supply and demand that occurs in the stock market (secondary market). The more investors who want to buy or save a stock, the price goes up, on the contrary more and more investors want to sell or release a stock, the price moves down. This study aims to analyze the effect of liquidity and profitability simultaneously on the stock prices of manufacturing companies in LQ-45; analyze the liquidity of the stock price of manufacturing companies in LQ-45 and analyze profitability against the stock price of manufacturing companies in LQ-45. The sample in this study were 8 companies during the period 2013 - 2017. The analysis technique used multiple regression analysis. The results of the analysis show that liquidity and profitability simultaneously influence stock prices, which means that the higher the company's liquidity and supported by increased profitability can increase the stock price of manufacturing companies in LQ-45. Partial liquidity partially affects stock prices, which means that the high level of liquidity of the company has an impact on the high and low stock prices of manufacturing companies in the LQ-45. Partial profitability partially affects stock prices, which means that high profitability is a consideration for investors in investing their funds on the stock exchange so that it has an impact on the increase in manufacturing company's stock prices on LQ-45.